Network Invulnerability Assessment Technology Based on the ENI - Yuanni Liu; Hong Tang; Guofeng Zhao; Yunpeng Xiao; Chuan Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, we have proposed a network invulnerability assessment technique based on the entropy of node importance (ENI) determined by the node betweenness combined with node degree, which can measure the network invulnerability dynamically. Simulation results show that the ENI network entropy can accurately change its values as the network nodes removed deliberately or randomly from the network, and ENI can estimate the network invulnerability accurately, as well as can reflect the damage degree of the network according to network entropy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2966